The Political and Religious Tensions of Fijian Dance in Canada: Renegotiating Identity Through Affect. (2014) - Kelly, Evadne
Abstract : Recent performances of meke, a "traditional" Fijian song-dance genre, in Canada indicate a renegotiation of identity among Fijians in diasporic communities. However, due to religious and political anxieties involving Fiji's colonial history, not all Fijians in Canada will participate in meke . To explore this, I draw from archival research and fieldwork conducted in Western Canada and Viti Levu, Fiji (2011–2012). Additionally, I take inspiration from the anthropological theory of affect, whereby the body has the ability to be affected (to feel/sense) and to affect others (causing others to feel/sense). I argue that experiences and expressions of powerful feeling states in and surrounding meke performance are important in terms of renegotiating Fiji's past colonial and present post-independence realities while negotiating new connections and relations in multicultural Canada.